SIFAT-SIFAT KOPAL MANILA DARI PEKALONGAN TIMUR DAN BANYUMAS BARAT - Yacob Ando; Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Manila copal is a natural rosin obtained by tapping Agathis trees. The resin is generally collected every other two weeks. In trade copal is known of three kinds namely: Caurry, Congo, and Manila Copal. Indonesian copal includes manila copal; is divided into four groups, among others: bua, loba, melengket, and pontianak copal.The moisture content of manila copal from East Pekalongan and West Banyumas was 1.74% and 1.85%; the colour, based on the LPHH standard ranked 3 and 2; impurities 2.47% and 2.49%; softening point 81°C and 92°C.; ash content 0.04% and 0.08%; acid number 118.93 and 139.71; saponification number 337.67 and 392.98; and iod number 36.5 and 42.98, repectively.Manila copal from East Pekalongan and West Banyumas appeared to have good quality and belongs to the first qualify based on the Indonesian Standard. Manila copal from West Banyumas has a higher resin acid content then that from East Pekalongan.